2016
DOI: 10.1080/14740338.2016.1199683
|View full text |Cite
|
Sign up to set email alerts
|

Drug safety evaluation of roflumilast for the treatment of COPD: a meta-analysis

Abstract: The safety profile of roflumilast administered in combination with further drugs for the treatment of COPD should be investigated through specifically designed RCTs, and the post-marketing surveillance might help to characterize the real risk of very SAEs. Roflumilast may provide more benefit than harm in patients at high risk of severe exacerbations, and the therapy discontinuation may be reduced by a correct education of patients on the generally transient and mild-to-moderate nature of gastrointestinal AEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 83 publications
(88 reference statements)
0
35
0
2
Order By: Relevance
“…Although methylxanthines have bronchorelaxant and anti-inflammatory effects in human patients with chronic obstructive pulmonary disorders [60], surprisingly this class of drugs was not effective in improving the lung function in equine asthma. Several PDE4 inhibitors have been investigated for their therapeutic potential in both human asthma and COPD and roflumilast received regulatory approval for use in patients with chronic bronchitis and a history of frequent exacerbations [18,61]. Although the current results indicate that the PDE4 inhibitor L-826,141 did not improve the lung function in horses, further well designed studies are needed before definitely considering PDE4 inhibitors ineffective in equine asthma.…”
Section: Discussionmentioning
confidence: 75%
“…Although methylxanthines have bronchorelaxant and anti-inflammatory effects in human patients with chronic obstructive pulmonary disorders [60], surprisingly this class of drugs was not effective in improving the lung function in equine asthma. Several PDE4 inhibitors have been investigated for their therapeutic potential in both human asthma and COPD and roflumilast received regulatory approval for use in patients with chronic bronchitis and a history of frequent exacerbations [18,61]. Although the current results indicate that the PDE4 inhibitor L-826,141 did not improve the lung function in horses, further well designed studies are needed before definitely considering PDE4 inhibitors ineffective in equine asthma.…”
Section: Discussionmentioning
confidence: 75%
“…Two separate meta‐analyses found that roflumilast is effective in reducing the number of exacerbations, and a full incremental analysis from the UK in 2012 concluded that roflumilast treatment is both clinical‐ and cost‐effective in the treatment of patients ‘continuing to exacerbate despite existing bronchodilator therapy’ . Identifying means to specifically select well‐responders to the treatment may consequently reduce the number of hospital admissions and lower the costs associated with COPD exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Roflumilast is a phosphodiesterase‐4‐inhibitor (PDE4), which was introduced to the European market in July 2010 . The drug was approved as a prophylactic treatment for COPD patients with frequent exacerbations and has been included in the Global initiative for chronic Obstructive Lung Disease (GOLD) guidelines . In such, patients with COPD must experience chronic cough and sputum production, as well as having a history of exacerbations before roflumilast is indicated .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphodiesterase-4 inhibitors are other anti-inflammatory agents, which inhibit the breakdown of intracellular cyclic AMP; they do not have direct bronchodilator activity, but improve FEV1 in patients treated with LABA and LAMA and reduce moderate and severe exacerbations with concomitant corticosteroids [5,48,49]. Long term treatment with macrolides may reduce exacerbations in severe COPD patients not controlled by inhalation therapy [50].…”
Section: The Co-morbidomementioning
confidence: 99%